Роль суду в забезпеченні законності правоохоронної діяльності митних органів - Додін, Євген Васильович; Додин, Евгений Васильевич; Dodin, Evgenij (My University, 2011)
The article examines the role and place of the courts to ensure the rule of law enforcement activity of customs authorities. Determined by the need to manage the existing jurisprudence of all jurisdictional authorities, and especially the customs authorities of Ukraine, taking into account the mobility of the customs legislation, decriminalization of commodity smuggling, the use of «special forfeiture,» etc. The author examines the importance of the recommendations of the Supreme Court of Ukraine, 1999 N 2, 2005, N 8, with decision-making in cases of customs violations.
Додін Є. В. Роль суду в забезпеченні законності правоохоронної діяльності митних органів / Є. В. Додін // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 91-100.
Keywords: митна злочинність; контрабанда; порушення митних правил; правовохоронна діяльність митних органів; таможенная преступность; контрабанда; нарушение таможенных правил; правоохранительная деятельность таможенных органов; customs crime; smuggling; violation of customs regulations; law enforcement, customs authorities